PERSEPSI DAN KESIAPAN DIRI MAHASISWA FAKULTAS KEDOKTERAN TERHADAP IMPLEMENTASI INTERPROFESSIONAL EDUCATION DI UNIVERSITAS SAM RATULANGI MANADO - Mario Esau Katuuk; Angelina Stevany Regina Masengi; Ollivia Enggelina Supit (Jurnal Ilmiah Keperawatan IMELDA, 2023)
The need for an interprofessional education learning system started from the complexity of health services and social services. It requires the effective coordination and collaboration of health professions. Higher education institutions providing health education are encouraged to implement interprofessional education system by conducting an assessment of student readiness and perceptions regarding interprofessional education system. The purpose of this study was to identify the perceptions and self-readiness of undergraduate students at the Faculty of Medicine, Sam Ratulangi University regarding the implementation of interprofessional education system. This research method uses a descriptive research design using a questionnaire distributed using an online form. Univariate data analysis was performed and results are presented in a frequency distribution table. The results showed that most of the respondents had a good perception of interprofessional education (97.9%), while 3% had an adequate perception. A relatively similar picture is found for self-readiness where 75.9% of respondents have good self-readiness, the rest are in the sufficient category (24.1%). It can be concluded that according to students' perceptions and self-readiness, shows that there are excellent opportunities for educational institutions to develop and implement interprofessional learning systems, especially in the health sector to improve communication and collaboration as well as health services quality.